SISTEM KEAMANAN RUMAH DAN BUKA PINTU MENGGUNAKAN KEYPAD BERBASIS ARDUINO - Nazarwati, Asra; Yunan, Amsar; Jannah, Dina Miftahul; Ihsan, M Arinal; Ihsan, Ihsan (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2024)
A house is a place to live that is a primary need for everyone. The house and its belongings must be protected from unwanted things such as criminal acts of theft. Seeing the frequent crimes committed by thieves targeting people's homes, whether they are left by their owners or not, makes people restless when they want to leave their homes unoccupied. Therefore, there is a need for a strong home system to prevent theft and implement how the home security system works and open the door using a matrix keypad. By using Arduino as a controller, the circuit will process input from the PIR sensor which functions as a motion detector sensor and keypad and as a tool to input pins or passwords that have been stored in the Arduino EEPROM, and then the Arduino will process the output in the form of a relay as a switch to activate the electromagnetic solenoid, with the working principle if the sensor detects a person who is about 3 to 5 meters from the sensor, the alarm will sound, and to open the door, you must input the password according to the password stored in the Arduino EEPROM, if the password is input correctly, the door will open, if the password is wrong, the door will not open.